Preparation method of high-ionic-conductance vacancy-rich Li3N solid electrolyte
Li3N with high empty space concentration was prepared by ball milling technology and combined with other solid electrolyte materials, which solved the problem of low ionic conductivity of Li3N solid electrolytes, achieving high ionic conductivity and excellent cycling performance.
Patent Information
- Application Number
- CN202411931115.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing all-solid lithium metal batteries, the ionic conductivity of Li3N solid electrolyte is low, resulting in insufficient resistance to lithium dendrites, and the preparation method is complex and costly.
By ball milling Li3N and ZrO2 balls under Ar atmosphere, Li3N powder with high vacancies and combined with solid electrolyte materials such as oxides to prepare a vacancies-rich Li3N solid electrolyte layer.
It achieves high ionic conductivity, reaching 2.08×10-3S cm-1, and has high stability and excellent cycling performance for lithium metal negative electrode sheets. It is suitable for a variety of solid electrolyte systems.
Smart Images

Figure CN119695263A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium metal batteries, and in particular to a method for preparing a high-ion-conductivity vacancy-rich Li3N solid electrolyte. Background Art
[0002] Compared with traditional lithium-ion batteries, all-solid-state lithium metal batteries provide new opportunities to replace flammable liquid electrolytes, meet demanding energy and power density, and high safety. However, when oxides, sulfides, and halides are used as solid electrolytes (SSEs), their research and development have encountered serious challenges in the application of negative electrode lithium metal, which is manifested in that lithium metal is prone to serious side reactions at the interface with unstable sulfides and halides at low voltages, and lithium dendrites are also easy to pass through the grain boundaries of oxides. In order to overcome these interface challenges, the application of effective coating or intermediate layer design to stabilize the lithium metal anode is a temporary remedy. The use of these coating strategies and intermediate layers usually involves complex methods or increases material costs and the complexity of the manufacturing process. Chinese patent application CN115706259A discloses a method for high-energy plasma interface modification of electrolytes, which uses high-energy plasma to etch, replace, and deposit elements on the surface of solid electrolytes, remove Li2CO3 and LiOH impurities on the surface of solid electrolytes, and treat the surface of solid electrolytes at the same time, which can quickly achieve doping of elements such as N and H or conversion synthesis of nitrides and hydrides, but the preparation method is complex and costly. Among them, Li3N SSE has been proven to be thermodynamically stable relative to lithium metal in all-solid-state lithium metal battery applications, but the lithium ion diffusion behavior in Li3N depends on the lithium vacancies in the crystal structure. The concentration of lithium and nitrogen vacancies in the inherent lattice structure of Li3N is low, resulting in low ion conductivity and insufficient resistance to the formation of lithium dendrites. CN117142855A discloses a preparation method for low-temperature sintering of a Li3N-doped garnet-type solid electrolyte sheet, wherein garnet-type oxide powder and lithium nitride additive are mixed according to a certain mass percentage and then cold-pressed, and then sintered at a relatively low temperature to obtain a solid electrolyte sheet, but the conductivity is limited. Summary of the invention
[0003] In order to overcome the defects in the prior art, an embodiment of the present invention provides a method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte, which is used to solve one or more of the above problems.
[0004] The embodiment of the present application discloses: a method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte, comprising the following steps: ball-milling Li3N and ZrO2 balls in a ball mill under Ar atmosphere; pressing the milled Li3N powder to obtain a Li3N film A; preheating the pressed Li3N film A and pressing it with a lithium metal negative electrode sheet B to obtain a composite sheet AB; grinding SSE powder and pressing it into a film C; pressing the pressed SSE film C with the surface of the Li3N film A facing away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer.
[0005] Furthermore, the thickness of the CA layer is 200 μm to 1200 μm, the thickness of the C layer is 100 μm to 600 μm, and the thickness of the A layer is 100 μm to 600 μm.
[0006] Furthermore, in the step of "ball milling Li3N and ZrO2 balls in a ball mill under Ar atmosphere", the diameter of the ZrO2 balls is 3 mm to 8 mm, and the mass ratio of the ZrO2 balls to the Li3N is 30 to 60.
[0007] Furthermore, the rotation speed of the ball mill is 300 rpm to 600 rpm, and the rotation time is 5 h to 14 h.
[0008] Furthermore, in the steps of "pressing the ball-milled Li3N powder to obtain Li3N film A", "grinding the SSE powder and pressing it into film C" and "pressing the pressed SSE film C and the surface of the Li3N film A facing away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer", the pressing pressure is 2 to 5T.
[0009] Furthermore, in the step of "preheating the pressed Li3N film A and pressing it with the lithium metal negative electrode sheet B to obtain a composite sheet AB", the preheating temperature is 60°C to 100°C, and the preheating time is 0.5h to 1h.
[0010] Furthermore, in the step of "preheating the pressed Li3N film A and pressing it with the lithium metal negative electrode sheet B to obtain a composite sheet AB", the pressure during pressing is 0.1T to 0.5T.
[0011] Furthermore, the SSE is an oxide, and the oxide SSE comprises one or more of garnet-type solid electrolyte materials, NASICON-type solid electrolyte materials, LISICON-type solid electrolyte materials, perovskite-type solid electrolyte materials and derivative materials thereof.
[0012] Furthermore, the SSE is a sulfide, and the SSE of the sulfide includes crystalline or amorphous Li2S-P2S5, crystalline Li4MS4, crystalline Li10 NP2S 12 , microcrystalline Li2S-P2S5-Li X and one or more of its derivative materials.
[0013] Furthermore, the SSE is a halide, and the halide SSE includes one or more of Li3YCl6, Li3YBr6, Li3InCl materials and their derivative materials.
[0014] The beneficial effects of the present invention are as follows:
[0015] 1. Ball milling technology is used to prepare Li3N with high vacancy concentration, and the vacancy-rich Li3NSSE in the solid electrolyte layer is highly stable to the lithium metal negative electrode sheet and has excellent cycle performance in all-solid-state batteries.
[0016] 2. According to the energy transfer theory, the preferred size and mass ratio of ZrO2, combined with the appropriate rotation speed and time, can produce suitable Li and N vacancies in Li3N.
[0017] 3. Achieve the effect of preparing Li3N with a high vacancy concentration and an ionic conductivity of 2.08×10-3S cm-1.
[0018] 4. SSE has a wide range of applications and is suitable for polymer, halide, sulfide and other systems.
[0019] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 It is a flow chart of a method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] like Figure 1 As shown, a method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte in this embodiment includes the following steps:
[0024] In an Ar atmosphere, Li3N and ZrO2 balls are ball-milled in a ball mill, thereby achieving the effect of ball-milling Li3N by ZrO2 balls in a ball mill to form Li3N powder. In this embodiment, Li3N is commercial Li3N.
[0025] The ball-milled Li3N powder is pressed to obtain a Li3N film A, which is then pressed with a lithium metal negative electrode sheet B to form a composite sheet.
[0026] The pressed Li3N film A is preheated and then pressed against the lithium metal negative electrode sheet B to obtain a composite sheet AB. By preheating the Li3N layer to a certain temperature and then facing the lithium metal negative electrode sheet and applying a certain pressure, good contact with the lithium metal negative electrode sheet can be ensured, so that the bonding effect of the composite sheet AB is better.
[0027] The SSE powder is ground and pressed into film C, which is convenient for subsequent pressing with Li3N film A to form a solid electrolyte layer.
[0028] The pressed SSE film C and the Li3N film A are pressed with the surface facing away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer.
[0029] By means of the above method, Li3N with a high vacancy concentration is prepared by ball milling technology, and the vacancy-rich Li3N SSE in the solid electrolyte layer is highly stable to the lithium metal negative electrode sheet and has excellent cycle performance in the all-solid-state battery.
[0030] Specifically, the thickness of the CA layer is 200 μm to 1200 μm, the thickness of the C layer is 100 μm to 600 μm, and the thickness of the A layer is 100 μm to 600 μm.
[0031] Specifically, in the step of "ball milling Li3N and ZrO2 balls in a ball mill under Ar atmosphere", the diameter of the ZrO2 balls is 3 mm to 8 mm, and the mass ratio of the ZrO2 balls to the Li3N is 30 to 60. Within the above range of the diameter of the ZrO2 balls and the mass ratio to Li3N, the milled Li3N has a higher vacancy concentration.
[0032] Specifically, the ball mill has a rotation speed of 300 rpm to 600 rpm and a rotation time of 5 h to 14 h, so that according to the energy transfer theory, the preferred size and mass ratio of ZrO2, combined with the appropriate rotation speed and time, can generate appropriate Li and N vacancies in Li3N.
[0033] Specifically, in the steps of "pressing the ball-milled Li3N powder to obtain Li3N film A", "pressing the SSE powder to form film C after grinding", and "pressing the pressed SSE film C and the surface of the Li3N film A away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer", the pressure during pressing is 2 to 5 T. Preferably, in the above steps, the pressure of each step can be kept the same. Of course, in other optional embodiments, the pressure of each step can also be adjusted to be different within the above range according to actual needs.
[0034] Specifically, in the step of "preheating the pressed Li3N film A and pressing it with the lithium metal negative electrode sheet B to obtain a composite sheet AB", the preheating temperature is 60°C to 100°C, and the preheating time is 0.5h to 1h. Preferably, the pressure during pressing is 0.1T to 0.5T. Under the above preheating temperature, time and pressing pressure, the Li3N layer is preheated to a certain temperature and faces the lithium metal negative electrode and is subjected to a certain pressure, which can ensure better contact with the lithium sheet.
[0035] Specifically, the SSE in this embodiment has a wide range of applications and is applicable to systems such as polymers, halides, and sulfides. The SSE may be an oxide, and the SSE of the oxide includes one or more of garnet-type solid electrolyte materials, NASICON-type solid electrolyte materials, LISICON-type solid electrolyte materials, perovskite-type solid electrolyte materials, and their derivative materials. The SSE may be a sulfide, and the SSE of the sulfide includes crystalline or amorphous Li2S-P2S5, crystalline Li4MS4, crystalline Li 10 NP2S 12 , microcrystalline Li2S-P2S5-Li X The SSE may be a halide, and the halide SSE includes one or more of Li3YCl6, Li3YBr6, Li3InCl materials and their derivative materials.
[0036] The present invention is described in detail below in conjunction with embodiments:
[0037] Embodiment 1:
[0038] Commercial Li3N and 4 mm ZrO2 balls were ball milled at 650 rpm for 12 h in an Ar atmosphere with a mass ratio of ZrO2 balls to Li3N of 40;
[0039] Next, 60 g of the ball-milled Li3N powder was placed on a PTFE mold and pressed at a pressure of 3 T to obtain a Li3N film A with a thickness of 350 μm and a diameter of 10 mm.
[0040] Next, the pressed Li3N film A was preheated at 90°C on a heating table for 0.5 h and then pressed with a 100 μm commercially available lithium metal sheet on a PTFE mold at 0.3 T to obtain a composite sheet AB.
[0041] Next, 50 g of Li3YCl6 SSE powder was ground and pressed into a film C with a thickness of 250 μm and a diameter of 10 mm at a pressure of 2 T;
[0042] Next, the pressed Li3YCl6 SSE film C and the back Li surface of the Li3N film A were pressed on a PTFE mold at a pressure of 2T to obtain a composite sheet CAB;
[0043] Next, the positive electrode NCM811 and Li3InCl6 powder were ground in a ratio of 7:3, a total of 10 g, and combined with the above-mentioned composite sheet CAB on the Li3YCl6SSE side, and pressed into sheets at a pressure of 3T. The thickness of the positive electrode layer was 70μm, and the mold was placed in a battery card slot with a stainless steel current collector to obtain a test battery.
[0044] Embodiment 2:
[0045] Commercial Li3N and 4 mm ZrO2 balls were ball milled in a ball mill at 450 rpm for 8 h under Ar atmosphere with a mass ratio of ZrO2 balls to Li3N of 40;
[0046] Next, 50 g of the ball-milled Li3N powder was placed on a PTFE mold and pressed at a pressure of 3 T to obtain a Li3N film A with a thickness of 300 μm and a diameter of 10 mm.
[0047] Next, the pressed Li3N film A was preheated at 80°C on a heating table for 0.5 h and then pressed with a 100 μm commercially available lithium metal sheet on a PTFE mold at 0.1 T to obtain a composite sheet AB.
[0048] Next, 65 g of Li3YCl6 SSE powder was ground and pressed into a membrane C with a thickness of 300 μm and a diameter of 10 mm at a pressure of 2.5 T;
[0049] Next, the pressed Li3YCl6 SSE film C and the back Li surface of the Li3N sheet A were pressed on a PTFE mold at a pressure of 2T to obtain a composite sheet CAB;
[0050] Next, the positive electrode NCM811 and Li3InCl6 powder were ground in a ratio of 7:3, a total of 10 g, and combined with the above-mentioned composite sheet CAB on the Li3YCl6SSE side, and pressed into sheets at a pressure of 3T. The thickness of the positive electrode layer was 70μm, and the mold was placed in a battery card slot with a stainless steel current collector to obtain a test battery.
[0051] Comparative Example 1:
[0052] 50 g of commercial Li3N powder was placed on a PTFE mold and pressed at a pressure of 3 T to obtain a 200 μm Li3N film A;
[0053] Next, the pressed Li3N sheet A was preheated at 80°C for 0.5 h on a heating table and then pressed with a 100 μm commercially available lithium metal sheet on a PTFE mold at 0.1 T to obtain a composite sheet AB.
[0054] Next, 65 g of Li3YCl6 SSE powder was ground and pressed into a membrane C with a thickness of 300 μm and a diameter of 10 mm at a pressure of 2.5 T;
[0055] Next, the pressed Li3YCl6 SSE film C and the back Li surface of the Li3N sheet A were pressed on a PTFE mold at a pressure of 2T to obtain a composite sheet CAB;
[0056] Next, the positive electrode NCM811 and Li3InCl6 powders were ground in a ratio of 7:3, a total of 10 g, and combined with the above-mentioned composite sheet CAB on the Li3YCl6SSE side, and pressed into sheets at a pressure of 3T. The thickness of the positive electrode layer was about 70μm. The mold was placed in a battery card slot with a stainless steel current collector to obtain a test battery.
[0057] Charge and discharge test:
[0058] The test batteries obtained in Examples 1, 2 and the comparative example were charged and discharged at room temperature using a constant current charging and discharging mode.
[0059]
[0060] The charge and discharge voltage range is 2.7~4.3V, 0.5C cycle 500 times, 1C=200mA / g, the test results are as follows:
[0061] It can be seen from the experimental results that the test batteries obtained by using Examples 1 and 2 of the present invention have higher capacity and more excellent cycle stability than the comparative example.
[0062] EIS test:
[0063] The test cells obtained in Examples 1, 2 and the comparative example were subjected to EIS (electrochemical impedance spectroscopy) testing at room temperature using a constant potential instrument from 7 MHz to 1 Hz with an amplitude of 10 mV. The test results are as follows:
[0064] Total impedance Example 1 70Ω Example 2 83Ω Comparison group 170Ω
[0065] It can be seen from the experimental results that the test batteries obtained by using Examples 1 and 2 of the present invention have lower impedance than the comparative example, and have greater advantages in battery cycle and rate.
[0066] Ionic conductivity test:
[0067] About 150 mg of powder sample was placed between two stainless steel rods with a diameter of 10 mm and pressed under a pressure of 3 T.
[0068] The particle thickness is 1.5 mm.
[0069] Ionic conductivity Example 1 <![CDATA[2.01×10 -3 Scm -1 ]]> Example 2 <![CDATA[2.08×10 -3 Scm -1 ]]> Comparison group <![CDATA[1.97×10 -5 Scm -1 ]]>
[0070] It can be seen from the experimental results that: compared with the comparative example, the ball milling technology makes Li3N produce suitable Li and N vacancies, which is more conducive to ionic conductivity, and the ball milling technology is used to prepare Li3N with a high vacancy concentration, so as to achieve the effect of preparing Li3N with a high vacancy concentration and an ionic conductivity of 2.08×10-3S cm-1.
[0071] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte, characterized in that: The following steps are involved: Li3N and ZrO2 balls were ball milled in a ball mill under Ar atmosphere; The ball-milled Li3N powder was pressed to obtain Li3N film A; The pressed Li3N film A is preheated and then pressed with the lithium metal negative electrode sheet B to obtain a composite sheet AB; The SSE powder was ground and pressed into film C; The pressed SSE film C and the Li3N film A are pressed with the surface facing away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer.
2. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: The thickness of the CA layer is 200 μm to 1200 μm, the thickness of the C layer is 100 μm to 600 μm, and the thickness of the A layer is 100 μm to 600 μm.
3. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: In the step of "ball milling Li3N and ZrO2 balls in a ball mill under Ar atmosphere", the diameter of the ZrO2 balls is 3 mm to 8 mm, and the mass ratio of the ZrO2 balls to the Li3N is 30 to 60.
4. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: The rotation speed of the ball mill is 300 rpm to 600 rpm, and the rotation time is 5 h to 14 h.
5. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: In the steps of "pressing the ball-milled Li3N powder to obtain Li3N film A", "grinding the SSE powder and pressing it into film C", and "pressing the pressed SSE film C and the surface of the Li3N film A facing away from the lithium metal negative electrode sheet to obtain a composite sheet CAB, wherein the CA layer serves as a solid electrolyte layer", the pressing pressure is 2 to 5T.
6. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: In the step of "preheating the pressed Li3N film A and pressing it with the lithium metal negative electrode sheet B to obtain a composite sheet AB", the preheating temperature is 60°C to 100°C, and the preheating time is 0.5h to 1h.
7. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: In the step of "preheating the pressed Li3N film A and pressing it with the lithium metal negative electrode sheet B to obtain a composite sheet AB", the pressure during pressing is 0.1T to 0.5T.
8. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: The SSE is an oxide, and the oxide SSE includes one or more of garnet-type solid electrolyte materials, NASICON-type solid electrolyte materials, LISICON-type solid electrolyte materials, perovskite-type solid electrolyte materials and derivative materials thereof.
9. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: The SSE is a sulfide, and the SSE of the sulfide includes crystalline or amorphous Li2S-P2S5, crystalline Li4MS4, crystalline Li 10 NP2S 12 , microcrystalline Li2S-P2S5-Li X and one or more of its derivative materials.
10. The method for preparing a high ionic conductivity vacancy-rich Li3N solid electrolyte according to claim 1, characterized in that: The SSE is a halide, and the halide SSE includes one or more of Li3YCl6, Li3YBr6, Li3InCl materials and their derivative materials.
Citation Information
Patent Citations
Method for high-energy plasma interface modification of electrolyte
CN115706259A
Low-temperature sintering preparation method of Li3N-doped garnet type solid electrolyte sheet
CN117142855A